Experimental and behavorial economics - Morgan, John (Advances in applied microeconomics, 2005)
As demand to substantiate predictions from economic theory with causal empirical evidence increases, economists have more and more turned towards controlled laboratory experiments. As this field has blossomed it has provided evidence confirming some of the key predictions of economic theory and exposed some of the weaker theoretical predictions. This has resulted in a symbiotic relationship where experimental evidence not only is used to support theoretical conclusions but has pointed economists into bold and exciting new areas of investigation. In this volume, I am proud to present some of the most stimulating work in this field. The first three chapters provide a fresh look at some of the classical issues in experimental economics. These papers provide novel insights into psychology in ultimatum games, the impact of social interaction on learning, and communication in coordination games. The next two chapters look at how experiments can illuminate our understanding of what determines trust. These papers examine how monitoring within an organization influences trust, as well as examining how individual political ideologies are related to an individuals level of trust. The final two chapters show how experiments can be fruitfully applied to vertical relationships and auction design, two of the most important areas in contemporary contract theory.